Digital health convergence meeting tool kit. - Roth, Susann; Parry, Jane; Thit, Win Min (Asian Development Bank, 2018)
This tool kit comprises information on how to create a shared vision for digital health through a national strategy, focused on maximizing the value of resources.It supports efforts to introduce digital health solutions that make systems interoperable and less fragmented, and thus provide equitable access to health care services and offer every patient continuity of care. This tool kit provides a practical framework for structuring digital health road maps, a guide to running a digital health convergence workshop, and insights from previous country convergence workshops.